Efficacy of Surgical Treatment of Peritoneal Carcinomatosis in Patients with Colorectal Cancer - T G Fetsych; A P Revura (Galician Medical Journal, 2016)
Colorectal cancer is one of the most common types of cancer in Ukraine. Prognosis for patients with peritoneal carcinomatosis is unfavorable, and life expectancy is typically less than 6 months. Cytoreductive surgery was introduced as a new method of treating these patients to prolong their survival time.